2021
DOI: 10.1186/s12909-020-02424-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motor imagery and actual practice on learning professional medical skills

Abstract: Background The peripheral venous catheter is the most frequently used medical device in hospital care to administer intravenous treatment or to take blood samples by introducing a catheter into a vein. The aim of this study was to examine the effect of motor imagery associated with actual training on the learning of peripheral venous catheter insertion into a simulated venous system. Method This was a prospective monocentre study in 3rd year medica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Insertion of a peripheral venous catheter is one of the most common medical invasive procedures used in hospitals and is frequently associated with nosocomial infections as a result of bacterial colonization of these foreign bodies within patients ( 48 , 49 ). We adopted a P. aeruginosa and S. aureus mixed biofilm-coated catheter model in mice ( 50 ) that allowed us to evaluate Peptide K6 for treatment efficacy of a polymicrobial infection under in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of a peripheral venous catheter is one of the most common medical invasive procedures used in hospitals and is frequently associated with nosocomial infections as a result of bacterial colonization of these foreign bodies within patients ( 48 , 49 ). We adopted a P. aeruginosa and S. aureus mixed biofilm-coated catheter model in mice ( 50 ) that allowed us to evaluate Peptide K6 for treatment efficacy of a polymicrobial infection under in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, González-Rosa et al [13] also found that AOP was more effective than MIP in promoting the early learning of a new complex coordination task. At the educational learning level, the research work conducted by Collet et al [21] showed that the application of MRS, in combination with physical practice, resulted in faster learning (in fewer sessions) than just physical practice alone. These results are in line with the results found in this research, showing that the application of MRS obtained better results than the real isolated practice, and, furthermore, that the AOP obtained better results in comparison with MIP.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no research work has been applied to improve specific learning of clinical techniques in the field of physiotherapy. Recently Collet et al [21] showed that medical students benefited from MIP training in clinical motor skills. The study conducted by Collet et al [21] is very interesting and opens up a range of possibilities for the study of motor learning in health science students using MRS. We hypothesize that MRS can be a tool for learning clinical techniques in physical therapy students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, although psychological assessment and questionnaires are probably the most accepted and validated methods in medical contexts [ 14 ], their inclusion in the automated prediction of the BCI skills remains very rare due to their disputed reliability and reproducibility [ 15 ]. For enhancing the predictive utility, the joint analysis of different imaging modalities is achieved, which may explain the discovered relationships between anatomical, functional, and electrophysiological properties of the brain [ 16 , 17 ]. Nonetheless, besides those issues that may arise by the questionary implementation, research endeavors of multimodal analysis pose a challenging problem in terms of combining categorical data with imaging measurements, facing the following restrictions [ 18 , 19 ]: Different spatial and temporal sampling rates, noninstantaneous and nonlinear coupling, low signal-to-noise ratios, a lack of interpretable results, and the optimal combination of individual modalities is still undetermined, as well as effective dimensionality reduction to enhance the discriminability of extracted multi-view features [ 20 ].…”
Section: Introductionmentioning
confidence: 99%